2020
DOI: 10.18632/oncotarget.27479
|View full text |Cite
|
Sign up to set email alerts
|

Mifamurtide and TAM-like macrophages: effect on proliferation, migration and differentiation of osteosarcoma cells

Abstract: Tumor-associated macrophages and their alternative activation states together with cytokines and growth factors trapped in tumor microenvironment contribute to the progression of OS. In contrast to other tumor types, M2 polarized macrophages, reduce metastasis and improve survival in osteosarcoma patients. Mifamurtide is an immunomodulatory drug given together with standard adjuvant chemotherapy in high-grade osteosarcoma to improve outcome. Macrophages obtained from peripheral blood mononucleated cells of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…At the same time, the inhibitory effect of activated M1-like macrophages on the growth of osteosarcoma cells is mediated by soluble factors [58]. The latest research shows that Mifamurtide regulates the function of macrophages by converting the polarization of macrophages to a TAM-like intermediate M1/M2 phenotype, thereby inhibiting the proliferation of osteosarcoma cells [59]. Consistent with previous results, our results show that patients in the low-risk group have a higher abundance of macrophage in ltration.…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, the inhibitory effect of activated M1-like macrophages on the growth of osteosarcoma cells is mediated by soluble factors [58]. The latest research shows that Mifamurtide regulates the function of macrophages by converting the polarization of macrophages to a TAM-like intermediate M1/M2 phenotype, thereby inhibiting the proliferation of osteosarcoma cells [59]. Consistent with previous results, our results show that patients in the low-risk group have a higher abundance of macrophage in ltration.…”
Section: Discussionsupporting
confidence: 91%
“…In phase II clinical trials mifamurtide induced the infiltration of activated macrophages into OS lung tissue metastases [ 143 ] with a marked difference in disease progression and overall survival [ 144 ] and that the mifamurtide-mediated M1-TAMs antitumor activity required IFN-γ [ 145 ]. Punzo et al demonstrated that, by switching macrophage polarization towards a TAM-like intermediate M1/M2 phenotype, mifamurtide may work by modulating macrophage functions and inhibit OS proliferation [ 102 ]. In order to enhance the activation of the immune response, the European Medical Agency (EMA) has approved the use of mifamurtide, as an adjuvant in combination with chemotherapy, for the treatment of OS patients [ 146 ].…”
Section: Tam and Os Therapymentioning
confidence: 99%
“…Macrophages are immune cells with a key role in inflammatory processes [ 8 , 9 , 10 ], and they are present in two distinct states of activation: the classically activated macrophages (M1) and the alternatively activated macrophages (M2) [ 9 , 10 , 11 ]. While M1 exert pro-inflammatory, anti-tumor, and anti-microbial properties, releasing pro-inflammatory cytokines [ 8 , 9 , 10 , 11 ], M2 show anti-inflammatory and immunosuppressive functions, releasing anti-inflammatory cytokines and promoting tumor progression [ 8 , 9 , 10 , 11 ]. The prevalence of M1 in ITP is responsible for both disease pathogenesis and impairment in inflammatory and immune responses [ 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages are activated by Tumor Necrosis Factor-α (TNF-α), Interferon-γ (IFN-γ), and bacterial lipopolysaccharide (LPS). They exert pro-inflammatory, anti-tumor, and anti-microbial functions, releasing high levels of pro-inflammatory cytokines, such as TNF-α, Interleukin-6 (IL-6), Interleukin-1β (IL-1β), and Nitric Oxide Synthase (iNOS) [ 8 , 9 , 10 , 11 ]. M2 macrophages are activated by Interleukin-4 (IL-4), Interleukin-13 (IL-13), Interleukin-10 (IL-10), and by Phosphatidylinositol 3-kinase-AKT-mammalian target of rapamycin (PI3K-Akt-mTOR) signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation